2007
DOI: 10.1073/pnas.0706378104
|View full text |Cite
|
Sign up to set email alerts
|

T helper 1 cells stimulated with ovalbumin and IL-18 induce airway hyperresponsiveness and lung fibrosis by IFN-γ and IL-13 production

Abstract: We previously reported that ovalbumin (OVA) and IL-18 nasally administered act on memory type T helper (Th)1 cells to induce airway hyperresponsiveness (AHR) and inflammation, which is characterized by peribronchial infiltration with neutrophils and eosinophils. Here, we report this administration also induces lung fibrosis in an IL-13-dependent manner. bronchial asthma ͉ LPS ͉ periostin ͉ hydroxy proline ͉ airway inflammation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
92
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(101 citation statements)
references
References 44 publications
8
92
0
1
Order By: Relevance
“…High levels of LPS have been detected in the bronchoalveolar lavage fluid (BALF) from steroidresistant asthmatics and are an important determinant of the severity of asthma (9,17). We and others have shown that IFN-g-producing cells and LPS contribute to the induction of airway inflammation and AHR in mouse models; furthermore, we have demonstrated that IFN-g/LPS-induced responses are steroid resistant (18,19). Our investigations revealed a novel interaction between IFN-g and LPS that leads to the activation of pulmonary macrophages and the induction of steroid-resistant AHR (19).…”
mentioning
confidence: 72%
“…High levels of LPS have been detected in the bronchoalveolar lavage fluid (BALF) from steroidresistant asthmatics and are an important determinant of the severity of asthma (9,17). We and others have shown that IFN-g-producing cells and LPS contribute to the induction of airway inflammation and AHR in mouse models; furthermore, we have demonstrated that IFN-g/LPS-induced responses are steroid resistant (18,19). Our investigations revealed a novel interaction between IFN-g and LPS that leads to the activation of pulmonary macrophages and the induction of steroid-resistant AHR (19).…”
mentioning
confidence: 72%
“…Thus, we were able to demonstrate that an important second signal, associated with the activation of innate host defense pathways by LPS, contributes to a mechanism whereby Th1 cells induce AHR and enhance the recruitment of pulmonary neutrophils. LPS has been previously shown to cooperate with Th cells of a mixed phenotype, which secrete both IFN-␥ and type 2 cytokines (e.g., IL-13 and IL-9) and induced eosinophilic (similar to Th2-induced responses) and neutrophilic inflammation in response to Ag challenge (27). In this model, IL-18 played a critical role in promoting the mixed Th phenotype and AHR but the role of neutrophils and macrophages and the steroid sensitivity of the response was not determined.…”
Section: Discussionmentioning
confidence: 99%
“…In some settings, Agspecific Th1 cells may induce AHR and features of allergic inflammation by IFN-␥ and IL-13 production (27). To determine the role of the IL-13/STAT6 pathway as a common downstream effector mechanism for AHR induced by Th2 and Th1 cells, we compared airway reactivity and inflammation in WT and STAT6 Ϫ/Ϫ mice treated with Th1/OVA plus LPS or IFN-␥ plus LPS (Fig.…”
Section: Ahr Induced By Th1 Cells and Lps But Not Th2 Cells Is Stermentioning
confidence: 99%
“…It has been generally accepted that Th2 cytokines such as IL-4, IL-5, IL-9, and IL-13 play critical roles in orchestrating and amplifying allergic inflammation in asthma. Th1 cytokine IFN-␥ was thought to prevent this process (2,3), however, recent studies indicate that IFN-␥ secreted by Th1 cells may cause severe airway inflammation under certain conditions (4,5).…”
mentioning
confidence: 99%